Risk culture evaluation: A case study of Islamic Bank XYZ - Meloza, Kausar; Chaerul Djusman Djakman (JIFA (Journal of Islamic Finance and Accounting), 2023)
In response to the 2007–2009 financial crisis and various instances of risk management failures impacting financial institutions, regulators and companies have become increasingly aware of the critical role that risk culture plays in enhancing the effectiveness of risk management within financial organizations. Recently, Bank XYZ has experienced a significant rise in losses due to operational incidents closely linked to aspects of its risk culture. This study utilizes the Financial Stability Board’s (FSB) Sound Risk Culture Indicators framework to assess the strength of the risk culture at Bank XYZ. Data was collected through questionnaires completed by 44 respondents, interviews with two senior leaders, and a review of relevant documents. The findings reveal that, overall, Bank XYZ demonstrates strong risk culture indicators, though there are areas for improvement, including: the articulation of leadership’s risk culture aspirations, the establishment of clear reporting channels for products and practices, the processing of significant past incidents as lessons learned, the systematic evaluation of risk culture aspects, and the strengthening of the control function's roles and authority in business decision-making. This study provides valuable insights into the resilience of an Islamic bank’s risk culture in Indonesia, using the FSB’s Sound Risk Culture Indicators.